Linked survey and statutory health insurance data evaluating healthcare utilization patterns and associated factors of persons with diabetes in Germany – latent class analysis - Ute Linnenkamp; Inga Deininghaus; Veronika Gontscharuk; Silke Andrich; Manuela Brüne; Nadezda Chernyak; Johannes Kruse; Mickaël Hiligsmann; Barbara Hoffmann; Andrea Icks (Scientific Reports)
Abstract Persons with diabetes mellitus have complex healthcare needs. Existing disease management programmes (DMPs) are based on a one-size-fits-all approach. However, individuals might require more individualised care. This study aims to identify groups with different patterns of healthcare utilization among people with diabetes in Germany and factors associated with these different patterns. A cross-sectional survey was conducted among a random sample from a statutory health insurance (SHI) with diabetes (n = 1332) and linked to longitudinal SHI data. Latent class analysis was used to identify subgroups with similar patterns of healthcare utilization and factors associated with different patterns. Four patterns of healthcare utilization were identified among people with diabetes: ‘low users’ (20.8% of the total sample); ‘low users with ophthalmologist visit’ (45.2%); ‘high users’ (26.5%); and ‘high users with mental health care’ (7.5%). The classes differed significantly in age, sex, type, duration and severity of diabetes, DMP membership, diabetes training, health-related quality of life, and prevalence of depression. The ‘high users with mental health care’ class was for example younger, more female, had a lower quality of life and the highest prevalence of depression. This study may provide a first basis for thinking about targeted care in Germany beyond DMPs.